B Cell Subsets as Severity-Associated Signatures in COVID-19 Patients - Sosa-Hernández, Víctor A.; Torres-Ruíz, Jiram; Cervantes-Díaz, Rodrigo; Romero-Ramírez, Sandra; Páez-Franco, José C.; Meza-Sánchez, David E.; Juárez-Vega, Guillermo; Pérez-Fragoso, Alfredo; Ortiz-Navarrete, Vianney; Ponce-de-León, Alfredo; Llorente, Luis; Berrón-Ruiz, Laura; et al. (Frontiers in Immunology, 2020)
Background. SARS-CoV-2 infection represents a global health problem that has affected millions of people. The fine host immune response and its association with the disease course have not yet been fully elucidated. Consequently, we analyze circulating B cell subsets and their possible relationship with COVID-19 features and severity. Methods. Using a multiparametric flow cytometric approach, we determined B cell subsets frequencies from 52 COVID-19 patients, grouped them by hierarchical cluster analysis, and correlated their values with clinical data. Results. The frequency of CD19+ B cells is increased in severe COVID-19 compared to mild cases. Specific subset frequencies such as transitional B cell subsets increase in mild/moderate cases but decrease with the severity of the disease. Memory B compartment decreased in severe and critical cases, and antibody-secreting cells are increased according to the severity of the disease. Other non-typical subsets such as double-negative B cells also showed significant changes according to disease severity. Globally, these differences allow us to identify severity-associated patient clusters with specific altered subsets. Finally, respiratory parameters, biomarkers of inflammation, and clinical scores exhibited correlations with some of these subpopulations. Conclusions. The severity of COVID-19 is accompanied by changes in the B cell subpopulations, either immature or terminally differentiated. Furthermore, the existing relationship of B cell subset frequencies with clinical and laboratory parameters suggest that these lymphocytes could serve as potential biomarkers and even active participants in the adaptive antiviral response mounted against SARS-CoV-2.